Abstract 4129675: Effective Transcatheter Intracoronary Delivery of mRNA-Lipid Nanoparticle Targeting on The Heart - Handa, Kazuma; Kawamura, Masashi; Sasai, Masao; Matsuzaki, Takashi; Harada, Akima; Miki, Kenji; Fujimura, Lisa; Saito, Shunsuke; Tsuneda, Ryo; Fujishiro, Anri; Hirano, Kunio; Miyagawa, Shigeru (Circulation (New York, N.Y.), 2024)
Introduction: mRNA has great potential to provide new medical innovations in the treatment of heart failure. Lipid nanoparticles (LNPs) are an established and effective mRNA delivery system. However, effectively delivering LNPs to the heart remains a significant challenge. We evaluated the efficacy of transcatheter intracoronary (IC) administration compared to intravenous (IV) and intramyocardial (IM) administration as methods for delivering. Methods: Normal rabbits were used to examine each route of administration. Fluorescence (ATTO 700)-labeled LNP encapsulating Firefly Luciferase (FLuc) mRNA (25 ug/kg) were used to confirm the in vivo mRNA-LNP dynamics. The LNP accumulation and FLuc expression were verified using an in vivo imaging system (IVIS) 4 hours post-administration, followed by immunohistochemical analysis. The same experiments were conducted in an ischemia-reperfusion (I/R) model. Results: In the normal model, IVIS spectrum data showed that LNPs accumulated in the order of IM, IC and IV groups, with FLuc expression significantly higher in the IC group than in the IV group and comparable to the IM group (A). Histological analysis revealed that FLuc-expressing cells were mainly found in troponin T-positive cardiomyocytes at the injection site in the IM group and throughout the heart in the IC group (B). In the I/R model, LNP accumulation and FLuc expression were increased in the IV group compared to the normal model, whereas, in the IC and IM groups LNP accumulation and FLuc expression levels were similar to those in the normal model (C). Histological analysis revealed more FLuc-expressing cells in the infarcted area in all groups, but higher FLuc expression was observed in remote areas in the IC group (D). Conclusions: IC administration effectively delivered mRNA-LNPs not only to the damaged area but also to the remote area (non-damaged area) in the diseased heart, suggesting a safe and useful method for delivery to a wider range of cardiomyocytes in the heart.